KEMAMPUAN ADAPTASI PADA BUDAYA MACCERA’ TAPPARENG BENCANA BANJIR DI KECAMATAN TEMPE KABUPATEN WAJO - Baso Witman Adiaksa (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: The purpose of this research is to know the influence of maccera tappareng culture on flood adaptation capability in Tempe Sub-district, Wajo Regency. Methods: Design of the research used, ie analytical survey with cross sectional approach. The population of this study were all household heads living and domiciled in Tempe Sub-district. especially in the Villages of Laelo, Salomengrafeng, Watalipue, and Matirrotappareng. As for the number of samples (as many as 90. Data were obtained by interview, observation, and questionnaire.The test used was Pearson test, chi-square, and logistic regression test 95% confidence with a = 0.05 Result: obtained calculated value p = 0,030 (smaller than a value = 0.05 Discussion: Maccerak Tappareng is the result of agreement of local people of Tempe Lake whose daily life is fisherman) Conclusion: The result can be interpreted that Ha accept or have cultural influence maccera 'tappareng on flood adaptation capability in Tempe Sub-district, Wajo Regency